How to write successful business & managemnet essays - Tissington, Patrick (Sage Publications Ltd, 2017)
How to Write Successful Business and Management Essays is a systematic guide to successfully producing written work for business and management degrees. The authors address the all-too-common pitfalls of essay assignments, as well as providing readers with a step-by-step program to approach essay questions, both in coursework and exam contexts. Relevance of writing skills to employability highlighted throughout. Additional content on researching a topic. New content on adapting writing for different audiences. New content on academic writing tips. Addition of useful websites. Additional coverage of plagiarism. More on critical evaluation. More on changing requirements through different levels of study.